Comparative Analysis of E-Commerce Platforms in Indonesia Using the SMART and TOPSIS Methods - Fakhri Fitra Al Taufiq (Jurnal Armada Informatika, 2026)
The rapid growth of e-commerce in Indonesia has been driven by increasing internet penetration and widespread smartphone usage. Tokopedia, Shopee, Lazada, Bukalapak, and Blibli remain the five most widely used platforms, each offering distinct advantages and limitations. However, the abundance of available platforms creates challenges for consumers in selecting the most suitable one, especially since multiple criteria—such as product price, transaction security, application usability, delivery speed, customer service, and product availability—must be considered simultaneously. To address this issue, this study employs a Decision Support System approach using Multi-Criteria Decision Making (MCDM) through the integration of the SMART and TOPSIS methods. Primary data were collected from 20 active e-commerce users who provided both importance weights for the evaluation criteria and performance ratings for each platform.The SMART method was used to normalize the criteria weights based on respondent prioritization. The results show that Transaction Security is the most influential criterion with a weight of 19.8%, followed by Product Availability at 19.4%. These weights were subsequently used in the TOPSIS calculation to determine each platform’s relative closeness to the ideal solution. The findings indicate that Shopee is the best-performing platform with a preference score of 0.911, followed by Tokopedia (0.825), Blibli (0.613), Lazada (0.188), and Bukalapak (0.000). This ranking demonstrates that Shopee consistently excels in high-weighted criteria, particularly product price, application ease of use, and product availability.Overall, the integration of SMART and TOPSIS proves to be effective in generating objective, measurable, and transparent recommendations for selecting the most suitable e-commerce platform based on user perceptions.